2009
DOI: 10.1051/0004-6361/200811417
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic orbits and variations of RS Ophiuchi

Abstract: Aims. The aims of our study are to improve the orbital elements of the giant and to derive the spectroscopic orbit for the white dwarf companion of the symbiotic system RS Oph. Spectral variations related to the 2006 outburst are also studied. Methods. We performed an analysis of about seventy optical and near infrared spectra of RS Oph that were acquired between 1998 and June 2008. The spectroscopic orbits were obtained by measuring the radial velocities of the cool component absorption lines and the broad Hα… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
138
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(152 citation statements)
references
References 22 publications
8
138
4
Order By: Relevance
“…Although the UV flux was several orders of magnitude greater than a normal symbiotic star and the ionization was sufficient to produce the O VI FUV doublet, no O VI Raman emission was detected at either spectral region during the time interval covered by these observations. This contrasts with the RS Oph 2006 outburst during which the 6825 Å line was detected (Brandi et al 2009;Iijima 2009) in the early stages after outburst (before day 60). Brandi et al note that the line was absent in quiescence.…”
Section: O VI Raman Line Profilescontrasting
confidence: 61%
See 1 more Smart Citation
“…Although the UV flux was several orders of magnitude greater than a normal symbiotic star and the ionization was sufficient to produce the O VI FUV doublet, no O VI Raman emission was detected at either spectral region during the time interval covered by these observations. This contrasts with the RS Oph 2006 outburst during which the 6825 Å line was detected (Brandi et al 2009;Iijima 2009) in the early stages after outburst (before day 60). Brandi et al note that the line was absent in quiescence.…”
Section: O VI Raman Line Profilescontrasting
confidence: 61%
“…Recurrent novae are produced by the initiation of a thermonuclear runaway provoked by accretion on massive WDs, which are nearer to the Chandrasekhar limit (for RS Oph, M WD ≈ 1.2 M ) than for normal symbiotics or symbiotic novae (<1 M ) (see Starrfield 2008;Anupama 2008;Mikolajewska 2008;Brandi et al 2009). The connection of these systems, and their supersoft XR emission after outburst, to SN Ia progenitors has long been a scenario (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These results, however, are based on 1-2 lines only except for He and Fe, and it is not clear (no line profiles available) whether their spectra are representative for the ejecta. On the other hand, Brandi et al (2009) observed strong narrow-line components and a broad pedestal in all emission lines on highresolution optical spectra taken 53-54 days after the 2006 outburst maximum which means that by then the red giant wind contribution to the line emission became significant.…”
Section: Uv and Optical Spectroscopymentioning
confidence: 93%
“…The supersoft phase exhibited by RS Oph also suggests that its WD is massive (Osborne et al 2011;Wolf et al 2013). RS Oph contains an M0-2 III mass donor (Dobrzycka et al 1996;Anupama & Miko lajewska 1999) in a binary with a 453.6 day orbital period (Brandi et al 2009). Brandi et al (2009) have presented compelling evidence for a massive WD in RS Oph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation